Managing Democracy in Malaysia (Identity, Minorities, and Representation) - Arik Dwijayanto; Yusmicha Ulya Afif; Khoirul Fathoni (ARISTO, 2020)
The Malaysian General Election (GE-14) in May 2018 raised an interesting and new phenomenon. For the first time since independence of Malaysia in 1957, the rulling alliance known as the National Front (Barisan Nasional, BN) which led by UMNO failed to secure simple majority in parliament and lost control of seven of Malaysia’s 13 states. This was due to the challenge presented by the new opposition alliance known as Pakatan Harapan (Alliance of Hope, PH) which won 113 of seats in parliament and gain control the central government. It is interesting that this significant increase in support for the opposition is due to their change the way minorities, identity and representation is managed. The Malaysian Supremacy as political manifesto of Pakatan Harapan which involves eradicating affirmative action based on etnicity, basing it instead on need, for instance need due to prosperity through the removal of government service tax (GST), and reformation of law. This would potentially increase the justice and equality for all ethnic or racial groups. This paper links the 2013 and 2018 elections, the more global trend in which minorities and youth representation  are standing up to demand their right and to the challenge multiracial presents in Malaysia as a Muslim country. Therefore, the fundamental questions in this paper of how Pakatan Harapan manage minorities, identity and representation within in the process of democracy and to what extent the opportunities and the involvement of youth as voters and parliamentary candidates in order to support a progressive democracy in Malaysia.